DNA Procedure of Dispute Paternity Case in Forensic Medicine and Medicolegal Department Airlangga University - Desy Martha Panjaitan; Ahmad Yudianto; Indah Nuraini (Universitas Muhammadiyah Yogyakarta, 2021)
Disputed Paternity cases are still prevalent in the society and they arise when a father claimed not to be the biological father of a child. It is important to resolve these cases because every child has the human right to be informed about their origin and legal status. Therefore, paternity or DNA test, which is a sophisticated development in science and technology is used to determine the biological father of a child. This study aims to determine the procedures of DNA test used for disputed paternity cases that was performed in Forensic Medicine and Medicolegal Department of Airlangga University. The materials used in this study include reviewing books, journals, and other relevant literature. The DNA test was able to find a gene match between the child and the biological father. In conclusion, the DNA procedures, in these cases were carried out in seven stages after taking samples from children, biological mother, and suspected fathers.